EVALUAREA HIDROLOGICĂ A BAZINULUI r. PRUT - Chirică, Lazăr (CEP USM, 2009)
The riverside of the Prut river has an important role in the development of the small and medium towns in the aria bymeans of water reserves, ecological state, degree of disruption. The infi nitesimal fl ow of the small rivers become vulnerable in the freshet periods and can cause immense fl oods.
Keywords: bazinulul Prut; reţeaua hidrografică Prut